Population and functional genomics of lactic acid bacteria, an important group of food microorganism: Current knowledge, challenges, and perspectives - Weicheng Li; Qiong Wu; Lai‐yu Kwok; Heping Zhang; Renyou Gan; Zhihong Sun (Food Frontiers, 2024)
Abstract Lactic acid bacteria (LAB) are widely used in the food industry, but little is known about their population genomics, hindering our understanding of their genetic background and evolution. To better understand the evolution of LAB and their potential applications to related food production, we conducted a scoping review of the literature focusing on genomic issues related to LAB. The research progress of LAB population and functional genomics was summarized by sorting the literature of LAB genomics research in the last 10–15 years. According to the existing evidence, the formation mechanism of characteristics of LAB and their habitat adaptive evolution directed by genome decay and horizontal gene transfer were elucidated. The major evolutionary driving forces of LAB are mutations and horizontal gene transfer (HGT) events with or without the involvement of mobile genetic elements instead of recombination. We also underline the application of LAB genome in food safety and properties. Collectively, this review paper provides up‐to‐date information of the population and functional genomics of LAB, current challenges in the field, and suggestions for improving the exploitation and application of LAB resources.